2015
DOI: 10.1186/s12885-015-1742-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of FOXP3+ tumor infiltrating lymphocytes in patients with breast cancer: a meta-analysis

Abstract: BackgroundThe prognostic significance of FOXP3+ tumor-infiltrating lymphocytes (TILs) in patients with breast cancer remains controversial. The aims of our meta-analysis are to evaluate its association with clinicopathological characteristics and prognostic significance in patients with breast cancer.MethodsPubMed, Embase, Cochrane Database and the Ovid Database were systematically searched (up to April 2015). The meta-analysis was performed using hazard ratio (HR), odds ratio (OR) and 95 % confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
5
49
0
1
Order By: Relevance
“…In agreement with previous findings, we demonstrated that both CD8+ and FOXP3+ cells were associated with good outcome in patients with TNBC, and that the clinical significance of FOXP3+ lymphocytes was highly dependent on the concurrent presence of cytotoxic T cells [2327]. Interestingly, when stratified based on the presence of CD8+ lymphocytes, a high infiltration of FOXP3+ cells trended towards reduced survival in TNBC patients with low numbers of CD8+ cells.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous findings, we demonstrated that both CD8+ and FOXP3+ cells were associated with good outcome in patients with TNBC, and that the clinical significance of FOXP3+ lymphocytes was highly dependent on the concurrent presence of cytotoxic T cells [2327]. Interestingly, when stratified based on the presence of CD8+ lymphocytes, a high infiltration of FOXP3+ cells trended towards reduced survival in TNBC patients with low numbers of CD8+ cells.…”
Section: Discussionsupporting
confidence: 91%
“…A high Tregs level was associated with poor prognosis in breast cancer [43] but with improved prognosis in colorectal cancer [44]. This study addressed the prognostic value of Tregs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst many of the included studies follow the TIL scoring method used by Denkert in 2010 [60], there is variation with some studies using H&E assessment [14,58,59,61,62,65], some using immunohistochemistry [63,64], and others using mRNA expression profiling [63]. Conclusions from some recent meta-analyses in this field [66,67] indicate that care must be taken when interpreting the results of studies of prognostic biomarkers. For example, it is suggested that FOXP3 + T regs correlate with poor prognosis in breast cancer [66,67], however T reg levels also correlate with other poor prognostic factors such as estrogen receptor-negativity, HER2-positivity, lymph node metastasis and high histological grade [6871].…”
Section: Tils In Invasive Breast Carcinomamentioning
confidence: 99%
“…Conclusions from some recent meta-analyses in this field [66,67] indicate that care must be taken when interpreting the results of studies of prognostic biomarkers. For example, it is suggested that FOXP3 + T regs correlate with poor prognosis in breast cancer [66,67], however T reg levels also correlate with other poor prognostic factors such as estrogen receptor-negativity, HER2-positivity, lymph node metastasis and high histological grade [6871]. Within the estrogen receptor-negative subgroup, high levels of FOXP3 + T regs may actually correlate with improved prognosis as markers of an active immune response [68,70].…”
Section: Tils In Invasive Breast Carcinomamentioning
confidence: 99%